2008
DOI: 10.1158/1078-0432.ccr-07-4544
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Angiogenesis Inhibition by Sunitinib on Tumor Distribution of Temozolomide

Abstract: Purpose: As combination chemotherapy of antiangiogenic agents with conventional chemotherapeutic drugs continues to evolve, an understanding of the pharmacokinetic and pharmacodynamic variables associated with optimal treatment is needed. Thus, the effect of the multitargeted tyrosine kinase inhibitor sunitinib on tumor distribution of temozolomide was investigated to evaluate conditions for optimal combination chemotherapy. Experimental Design: In mice bearing SF188V+ human glioma xenografts, measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 38 publications
2
93
1
2
Order By: Relevance
“…Previous studies have shown that sunitinib and bevacizumab cause downregulation of Ang-2 mRNA in human tumor cells including glioma and rectal cancer xenografts. 36,37 These reports and this study suggest that inhibitors of VEGF(R) signaling may decrease Ang-2 expression in tumors, which subsequently results in a decline of circulating Ang-2. In addition, inhibition of VEGF(R) signaling may reduce shedding of sTie-2, which is exclusively expressed on endothelial cells as described for RCC, 30 thereby decreasing endothelial cell binding of Ang-2 to its receptor.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies have shown that sunitinib and bevacizumab cause downregulation of Ang-2 mRNA in human tumor cells including glioma and rectal cancer xenografts. 36,37 These reports and this study suggest that inhibitors of VEGF(R) signaling may decrease Ang-2 expression in tumors, which subsequently results in a decline of circulating Ang-2. In addition, inhibition of VEGF(R) signaling may reduce shedding of sTie-2, which is exclusively expressed on endothelial cells as described for RCC, 30 thereby decreasing endothelial cell binding of Ang-2 to its receptor.…”
Section: Discussionsupporting
confidence: 55%
“…In further analysis, we determined whether there was a relationship between circulating Ang-2 levels and other proteins. It appeared that circulating Ang-2 levels were positively associated with most proteins, being levels of VEGF (Spearman' 36). In the separate analysis in 20 patients with relatively high levels of circulating Ang-2, these were also positively associated with sTie-2 levels…”
Section: Plasma Protein Concentrations At Baselinementioning
confidence: 96%
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…In addition, elegant preclinical work examining the role of Yuan et al 1996;Tong et al 2004;Dickson et al 2007b;Taguchi et al 2008;Falcon et al 2009;Juan et al 2009;Kamoun et al 2009;Chae et al 2010;Koh et al 2010;Primo et al 2010. b Jain et al 1998;Izumi et al 2002;Delmas et al 2003;Qayum et al 2009. d Inai et al 2004;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Dings et al 2007;Fischer et al 2007;Zhou et al 2008;Falcon et al 2009;Juan et al 2009;Kamoun et al 2009;Ohta et al 2009;Zhou and Gallo 2009;Chae et al 2010;Primo et al 2010. Lee et al 2000;Winkler et al 2004;Dings et al 2007;Fischer et al 2007;Eichhorn et al 2008;Batra et al 2009;Skuli et al 2009;McGee et al 2010.…”
Section: Vegfmentioning
confidence: 99%
“…As a reinforcing factor for tumor angiogenesis, Ang-2 is closely connected with the number and density of blood vessels, and the size, infiltration, and metastatic ability of tumor (Zhou et al, 2008;Pohl et al, 2008;Sun et al, 2011). It was previously confirmed that the expression level of the Ang-2 protein was correlated with the infiltration depth of colorectal cancer in intestinal wall, as well as its metastasis by blood vessels and clinical staging (Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%